The Strategic Role of Village-Owned Enterprises (BUMDS), Villages, and the Private Sector in Developing Granulated palm sugar Production in Central Java - Endang Purwaningsih Basrowi; Basrowi Basrowi; Tsalitsa Afifah Nidaul Haq (Lembaga Penelitian Universitas YARSI, 2026)
This study examines the problem of suboptimal partnerships among Village-Owned Enterprises (BUMDes), village governments, and the private sector in developing palm sugar production in Sempor Village, Kebumen. The novelty of this research lies in proposing a collaborative partnership model based on local wisdom that integrates regulatory, managerial, technological, and village cooperative institutional functions to support sustainable local economic development. The study addresses a gap in previous research, which has generally examined stakeholders' roles separately without offering an integrated collaboration model. A qualitative case study approach was employed. The research stages included problem identification, data collection through in-depth interviews, field observations, and document analysis, followed by data reduction, data display, and thematic analysis. The findings reveal that partnership effectiveness is influenced by clear role distribution, institutional capacity, stakeholder trust, and regulatory and technological support. The study concludes that an adaptive collaborative partnership model can strengthen palm sugar production governance and enhance the competitiveness of the rural economy. The managerial implication highlights the importance of strengthening cross-sector coordination and village institutions, while the study contributes a collaborative partnership model that can be replicated for the development of other leading rural commodities in Indonesia